Exploring the Feasibility of Sorghum Farming in South Africa Using Garrett’s Ranking Technique - Zamaswazi Nkosi; Nyankomo Marwa; Olawale Olufemi Akinrinde (Agriculture)
The potential for sorghum to be the driver of economic development in Sub-Saharan economies, including South Africa, is enormous. However, there has been a notable decline in the production, use, and consumption of sorghum due to the changes in preferences and lifestyle of its consumers in Southern Africa. While existing and extant studies have studied the benefits and impacts of sorghum on the African economy, there is an inadequate understanding of the feasibility of sorghum farming in South Africa using Garrett’s ranking technique. As a result, this study explores the feasibility of sorghum farming in the Nyoni area of KwaZulu Natal, South Africa. Hence, a survey was conducted with a sample size of 150 respondents that were purposively selected. An interview schedule was also used to collect primary data, and the data were analyzed using Garrett’s ranking technique. The results of this study indicated that edaphic factors, climatic factors, volatile markets, information transfers, education, drought resistance variety, access to credit, and technological advancement were critical in making sorghum farming feasible in the Nyoni area of KwaZulu Natal. Therefore, this study recommends that there is an overarching need to explore the feasibility of sorghum farming, starting at a smaller scale until a more stable state of marketability and potential profitability has been established.